Ungkapan Makian Bahasa Minangkabau dalam Interaksi Anak Muda di Nagari Limo Koto Kecamatan Koto VII Kabupaten Sijunjung - Fathiya Aqilah; Novia Juita (Persona: Kajian Bahasa dan Sastra, 2023)
The purpose of this study was to describe: (1) the forms of swear expressions, (2) the categories of swear expressions, and (3) the function of swear expressions in the Minangkabau language in the interaction of young people in Nagari Limo Koto, Koto VII District, Sijunjung Regency. The data source for this research is young people, especially junior high school/equivalent and high school/equivalent students in Nagari Limo Koto, Koto VII District, Sijunjung Regency. This type of research uses qualitative research with descriptive methods. The research data is in the form of utterances that contain forms, categories, and functions of swear expressions in the Minangkabau language used by young people in Nagari Limo Koto, Koto VII District, Sijunjung Regency in their interactions. The method used is the method of listening to the tapping technique. The data were then analyzed in the following stages: (1) transcribing the recorded data into written language, (2) identifying the data according to the identification table, (3) classifying the data into forms, categories, and functions of swear expressions, and (4) make conclusions based on research data. The results of this study, namely (1) the form of swear expressions, consists of three forms, namely (a) words, (b) phrases, and (c) clauses; (2) categories of swear expressions, consisting of three categories, namely (a) noun categories, (b) verbs, and (c) adjectives; (3) the function of swearing, consisting of six functions, namely (1) to express resentment, (2) to express strong resentment, (3) to express jokes or jokes, (4) to express intimacy in association, (5 ) to express insults, and (6) as a substitute for a person's name or nickname.